Strategic VMI Adoption in LSP Operations: Minimizing Truck TAT in JIT Supply Chains - Rajesh, Adithya Narayanan (ExcelingTech, 2025)
This study explores the evolution of Vendor Managed Inventory (VMI) within the supply chain of a large-scale motorcycle manufacturer, tracking its progression from a traditional non-VMI model to a centralized VMI system, and eventually to a decentralized, logistics service provider (LSP)- integrated framework. It examines the challenges associated with each VMI model, key structural changes, and the innovative solutions that enabled the company to overcome operational challenges. The shift to a centralized VMI model led to increased transportation costs and supplier resistance, limiting its overall effectiveness and prompting the company to adopt an LSP-integrated VMI framework. This decentralized approach balances cost efficiency with improved supplier collaboration, making it well- suited for manufacturers with geographically dispersed supplier networks. The study also analyzes issues related to last-mile delivery—particularly high truck turnaround time (TAT) in a Just-In-Time (JIT) environment—and how the implementation of a Logistics Control Tower (LCT), along with other strategic initiatives, helped reduce TAT from eight hours to four. The findings offer actionable insights for manufacturers aiming to enhance inbound logistics through effective VMI models, while addressing common implementation challenges with practical, real-world solutions. The study also contributes to the existing body of knowledge on VMI by introducing a decentralized framework integrated within LSP operations.